Common bean (Phaseolus vulgaris L.). Africa Regional Genebank: Securing germplasm for Africa - Mukankusi, Clare; Amongi, Winnyfred (2022)
The gene bank was established in 2012 to support Africa-wide bean research programs under Pan Africa Bean Research Alliance (PABRA) by preserving and managing germplasm. Accessions are utilized in various hybridization and other common bean research programs worldwide. Germplasm is accessible to all bean scientists.